Density-dependent effects on body size, Philopatry, and dispersal in the Damaraland mole-rat (Fukomys damarensis) - Finn, Kyle T (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
Population density may exert changes in a variety of behavioural and physiological characters in animals. However, the effects of density-dependence and dispersal are poorly studied in subterranean rodents due to the difficulties involved in observing such effects in wild populations. Using the cooperative breeding Damaraland mole-rat (Fukomys damarensis) as a model species, the effects of population density on body size, growth rates, group size, recruitment, philopatry and dispersal were investigated at two sites (one with low density and one with high density) in the Northern Cape of South Africa. Group size, litter size and the probability of recapture were independent of population density. However, individual body size, recruitment, dispersal rate and dispersal distance were density-dependent. Individuals were significantly larger, juveniles exhibited a significantly higher growth rate, and juvenile recruitment was significantly greater when population density was low. At higher densities, significantly more individuals were lost between capture events which may be indicative of increased rates of dispersal. Mean dispersal distances in mole-rats were reduced at higher densities and increased at lower densities. While both sexes dispersed equally, males were significantly more likely to join an established colony and females created new burrow systems. In addition, four times as many single females were found when population density was low. The apparent differences in the study populations may be attributed to variable annual rainfall or food availability. The greater annual rainfall at the high-density site may provide better habitat conditions and therefore result in an increase in the population density and an increased dispersal rate due to the relaxed ecological constraints such as reduced energetic costs to burrowing. However, the larger body size found at the low-density site may indicate that the available food at that location is of better quality. This study revealed that mole-rats were able to disperse over 1km and therefore a much larger study area would be required in capture-mark-recapture studies to ensure the recapture of the majority of dispersers. Lastly, a surprising find of this study was that females may survive a solitary existence for over two years while awaiting the arrival of a mate.
Keywords: Fukomys damarensis; Fukomys damarensis -- Reproduction; Fukomys damarensis -- Growth; Rodents -- Reproduction -- South Africa -- Northern Cape; Rodents -- Growth -- South Africa -- Northern Cape; Rodent populations -- South Africa -- Northern Cape